Thermal stability, dynamic mechanical analysis and flammability properties of woven kenaf/polyester-reinforced polylactic acid hybrid laminated composites - Azlin, M. N. M.; Sapuan, S. M.; Zuhri, M. Y. M.; Zainudin, Edi Syams; Ilyas, R. A. (Multidisciplinary Digital Publishing Institute, 2022)
This paper presents the thermal and flammability properties of woven kenaf/polyester-reinforced polylactic acid hybrid laminated composites. The effects of the fiber content and stacking sequences of hybrid composites were examined. The hybrid composites were fabricated using the hot press method. Thermogravimetric analysis, differential scanning calorimetry, dynamic mechanical analysis, and flammability properties of woven kenaf/polyester-reinforced polylactic hybrid composites were reported. The thermal results have demonstrated the effect of the hybridization of the composites on the thermal stability and viscoelastic properties of the laminates. The work also measured the burning rate of the hybrid composites during the flammability test. The S7 sample that consisted of all woven kenaf layers in composite recorded the highest char residue of 10%, and the S8 sample displayed the highest decomposition temperature among all samples. However, as for hybrid composites, the S5 sample shows the optimum result with a high char yield and exhibited the lowest burning rate at 29 mm/min. The S5 sample also shows the optimum viscoelastic properties such as storage and loss modulus among hybrid composites.